EXPLORING THE 212 REUNION MOVEMENT: LACK OF TACTICAL INNOVATION AND DECLINING MASS PARTICIPATION - Azmi, Mohammad Fazrulzaman (Aliansi, 2025)
After the 2016 Islamic Defense Action, the 212 Reunion Movement emerged to maintain the euphoria of the December 2, 2016 movement. However, why did this movement decline, and what factors explain it? To answer this question, this research used qualitative methods and process tracing analysis to compare the events of the 212 Reunion Movement from 2017 to 2023. The 212 Reunion Movement declined because they lost momentum to strengthen political influence. For instance, in 2016 and 2017 their momentum was the blasphemy case and the Jakarta elections. Then, in 2018 their momentum was the presidential election. This phenomenon occurred due to several factors, such as the lack of tactical innovation, the strengthening of government repression in restricting the 212 Reunion movement, the decline in government facilitation of the 212 Reunion movement, and the decline in mass participation.